2001
DOI: 10.1253/jcj.65.251
|View full text |Cite
|
Sign up to set email alerts
|

Combined Revascularization Strategy for Acute Myocardial Infarction in Patients With Intracoronary Thrombus

Abstract: rimary percutaneous transluminal coronary angioplasty (PTCA) for acute myocardial infarction (AMI) is a superior revascularization technique over systemic 1-4 or intracoronary 5 thrombolysis, although several limitations still remain, including a high reocclusion rate 6 or flow disturbance, 7,8 which influence the short 9,10 and long-term prognosis. 11 As is well known, the culprit lesion of AMI is usually a composite of atherosclerotic plaque and thrombus. [12][13][14] The thrombus burden varies from case to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Although the efficacies of embolic protection and mechanical thrombectomy devices [29,30] are vague, other preventive measures aimed at improving myocardial reperfusion at the microvascular level may be initiated prospectively and prove beneficial. Administration of a glycoprotein IIB/IIIA inhibitor, an intracoronary thrombolytic agent, or a high-dose adenosine infusion before pPCI was shown to be beneficial in some studies [31][32][33]. Additionally, ischemic postconditioning, circulatory support, and an earlier re-opening of the IRA and restoration of blood flow may produce noticeable positive results.…”
Section: Discussionmentioning
confidence: 99%
“…Although the efficacies of embolic protection and mechanical thrombectomy devices [29,30] are vague, other preventive measures aimed at improving myocardial reperfusion at the microvascular level may be initiated prospectively and prove beneficial. Administration of a glycoprotein IIB/IIIA inhibitor, an intracoronary thrombolytic agent, or a high-dose adenosine infusion before pPCI was shown to be beneficial in some studies [31][32][33]. Additionally, ischemic postconditioning, circulatory support, and an earlier re-opening of the IRA and restoration of blood flow may produce noticeable positive results.…”
Section: Discussionmentioning
confidence: 99%
“…Although preventive effects of embolic protection and some mechanical thrombectomy devices have been disappointing in setting of STEMI [27][28][29], preventive administration of some drugs before PCI may be helpful. The use of GPI reduced the rate of no-reflow [30,31], and intracoronary thrombolytics or adenosine infusion prior to PCI showed to be beneficial in prevention of no-reflow in small studies [32,33]. Furthermore, the TAPAS study recently suggested that the adjunct of thrombectomy using 6-French Export Aspiration Catheter was associated with improvement of myocardial reperfusion, which translated into substantial improvement of the clinical outcome at 12-month follow-up as compared with conventional primary PCI [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In cases of acute coronary syndrome (ACS), this phenomenon also occurs with considerable frequency even in native coronary arteries. 11,12 However, the frequency of embolized debris in routine PCI of native vessel has not been evaluated. The first clinical results of the effectiveness and safety of the AngioGuard Emboli Capture Guidewire (Cordis, Johnson and Johnson) was recently reported in a study by Eberhard et al 13 in which not only 11 SVG lesions, but also 15 native vessel lesions were enrolled and all cases were electively treated.…”
Section: Discussionmentioning
confidence: 99%